PERANCANGAN SISTEM PENGGERAK TRAINER TRANSMISI MANUAL 5 PERCEPATAN TOYOTA KIJANG - Mohammad Munib Rosadi, Retno Eka Pramitasari, Ali Hasbi Ramadani (Universitas Hasyim Asy'ari, 2019)
The need for learning media in the Machine Element II course makes the transmission trainer to be immediately presented in order to become a means of supporting student learning. In a transmission trainer system a driving mechanism is needed so that the transmission can rotate. The drive mechanism must be reliable to ensure the transmission can rotate without constraints. Therefore, it is necessary to design and calculate in designing the transmission driving mechanism. The purpose of this study was to determine the design and calculation of the transmission trainer drive system. The design results show that the required motor specs are motors with 250 watts of power, driven pulley diameter 50 mm, driven pulley diameter 250 mm, distance between pulley axes is 335 mm. use v-belt type A with a length of 1175 mm. this drive system mechanism will produce a final torque of 393.01 kg.mm which is considered good because it is higher than the planned torque that is 325,85 kg.mm.